THE SPECIFICS OF DISCLOSING THE SEMANTICS OF TRANSFORMATION WITHIM OBJECT-TRANSFORMATIVE AND SUBJECT-TRANSFORMATIVE SUBFRAMES - ZVONKO, Hanna (Linguistic and Conceptual Worldviews, 2024)
The article highlights the specifics of revealing the semantics of transformation in object-transformative and subject-transformative subframes.The object-transformative subframe is objectified in the Ukrainian language as a polypropositional model S – (V) – O = (R), where the transformation situation arises as the actions of the subject causing a change in the object. The subject performs certain manipulations that cause the transformation of one object into another. The corresponding verbal sentence is also polypropositional.The subject-transformative subframe is objectified in the Ukrainian language as a monopropositional model S1 – V – S2 = (R), where the transformation situation arises as a state of affairs in which the subject undergoes changes, transitions into a new quality, ceases to be itself. This new quality, expressed by a noun, is an obligatory part of the information about the subject in the expression, i.e., the meaning of the predicate here consists of the semantics of "transformation" and "new quality". The subject-transformative sentences, which objectify the subject-transformative subframe, are one of the linguistic forms of expressing the semantics of transformation in the Ukrainian language. The corresponding verbal sentence is also monopropositional.The concept of TRANSFORMATION in the subject-transformative frame is objectified by semantically heterogeneous sentences, among the general meanings of which we distinguish: 1) actual transformation; 2) change; 3) shifting of attention focus; 4) evaluative meaning. These types of meanings are interconnected and mutually intersect. Different nuances of transformation in subject-transformative sentences are conveyed by linking verbs (peretvoriuvatysia, peretvorytysia, stavaty, staty, robytysia, zrobytysia, obertatysia, obernutysia, perekydatysia, perekynutysia, perekhodyty, pereity).
Keywords: cognitive linguistics, concept TRANSFORMATION, semantics of transformation, transformative frame, object-transformative subframe, subject-transformative subframe